2018
DOI: 10.2482/haigan.58.122
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pulmonary Adenocarcinoma with Large Skin Metastasis That Showed a Remarkable Response to Nivolumab Therapy

Abstract: Background. Case. Conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…11 Ohashi et al reported that cutaneous metastasis of lung cancer shrank markedly after fifth-line treatment with nivolumab. 12 However, Hasan et al reported no efficacy for cisplatin and gemcitabine followed by atezolizumab for cutaneous metastasis of bladder urothelial carcinoma. 13 In our case, cutaneous metastasis emerged during treatment with platinum-based chemotherapy, and progressed rapidly during immunotherapy with pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Ohashi et al reported that cutaneous metastasis of lung cancer shrank markedly after fifth-line treatment with nivolumab. 12 However, Hasan et al reported no efficacy for cisplatin and gemcitabine followed by atezolizumab for cutaneous metastasis of bladder urothelial carcinoma. 13 In our case, cutaneous metastasis emerged during treatment with platinum-based chemotherapy, and progressed rapidly during immunotherapy with pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…reported that cutaneous metastasis of lung cancer shrank markedly after fifth‐line treatment with nivolumab. 12 However, Hasan et al . reported no efficacy for cisplatin and gemcitabine followed by atezolizumab for cutaneous metastasis of bladder urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%